Efficacy of endoscopic triage during the Covid-19 outbreak and infective risk. Issue 10 (October 2020) - Elli, Luca; Tontini, Gian Eugenio; Filippi, Elisabetta; Scaramella, Lucia; Cantù, Paolo; Vecchi, Maurizio; Bertè, Roberto; Baldassarri, Annarita; Penagini, Roberto
Abstract : Objective: SARS-CoV-2 outbreak is spreading worldwide. As a consequence of the new circumstances, almost all endoscopic units underwent in-depth reorganization involving patients' selection. We analyzed the efficacy of the newly adopted endoscopic triage. Methods: In March 2020, we monitored endoscopies to evaluate the effects of the novel selective triage aimed to reduce the number of investigations and viral spread/contagions. Clinical-demographic data of the patients, indications, type of endoscopy, endoscopic findings (subtyped in major and minor), finding rates (major and minor) and diagnostic yields (major findings) have been analyzed and compared to the endoscopic procedures performed in March 2019. Furthermore, patients were called at least 21 days after the endoscopy to evaluate the possibility of a Covid-19 onset. Results: Accordingly to the novel triage, the number of procedures dropped from 530 to 91 (−84%). The finding rates and diagnostic yields were 83% (74–89) vs 71% (66–73) ( P 0.015) and 56% (46–65) vs 43% (38–47) ( P 0.03) on March 2020 and March 2019, respectively. A significant increase of operative procedures has been reported in 2020, 34% vs 22% in March 2019. All the patients were recalled and neither cases of onset of Covid-19 like symptoms nor positive nasopharyngeal swabs PCR have been evidenced. Conclusion: The novel endoscopic triage significantly reduced the number of procedures and increased finding rates and diagnostic yields. However, a careful schedule of canceled procedures should be applied to avoid to miss relevant pathologies. No Covid-19 onset or infection has been noted after endoscopies. Abstract : Supplemental Digital Content is available in the text.